Developing an Innovative Gasification Based Bio-char Stove in Nepal - Shahi, Bishal; Thapa, Bishan; Chuhan, Ghanashyam; Bajracharya, Tri Ratna (Journal of the Institute of Engineering, 2014)
This paper on Nepali bio-char stove is a genuine effort to make the cooking practice in Nepal cleaner, efficient and cost effective. The main aim of the project was to develop a bio-char yielding gasifier stove so that not only user is benefited by clean, efficient and cost effective cooking also benefited by the by product of stove famously called bio-char which is reported to be a fertilizer. So, to meet the above two objectives, the stove was designed. The thermal efficiency of the stove was recorded to be 34%. The total cost of fabrication is NRs. 2500. NPV is positive, payback period is 6 months and 1 day and IRR is found to be 190%.The calorific value of charcoal obtained from the stove is found to be 6363 kcal/kg. The design, test results and analysis are presented in this paper. DOI: http://dx.doi.org/10.3126/jie.v10i1.10875 Journal of the Institute of Engineering, Vol. 10, No. 1, 2014, pp. 25–33